2019
DOI: 10.29333/ejmste/105637
|View full text |Cite
|
Sign up to set email alerts
|

The Energy Concept and its Relation to Climate Literacy

Abstract: Climate change is one of the most significant socio-scientific challenges of this century. To address this challenge, people need to be empowered to assess information about climate change and make informed decisions. Both aspects are covered by the concept of climate literacy. Many phenomena in the context of climate change, such as the greenhouse effect, are based on energy related processes. Thus, we assume that for dealing with climate change in education the understanding of the energy concept is essentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…It defines one's ability to understand and interpret thoughts in an informed manner as pertains to a specific subject matter (Milér and Sládek, 2011). Climate literacy qualifies one's ability to understand anthropogenic impact on socio-ecological systems (SES) leading to climate change, and how climate change affects life on earth (Mittenzwei et al, 2019).…”
Section: Innovative Climate Literacy and Citizen Sciencementioning
confidence: 99%
“…It defines one's ability to understand and interpret thoughts in an informed manner as pertains to a specific subject matter (Milér and Sládek, 2011). Climate literacy qualifies one's ability to understand anthropogenic impact on socio-ecological systems (SES) leading to climate change, and how climate change affects life on earth (Mittenzwei et al, 2019).…”
Section: Innovative Climate Literacy and Citizen Sciencementioning
confidence: 99%
“…A study which involved Chinese respondents both in the UK and China found that participants formed new habits like avoiding charging mobile phones at night and participating in green environmental public programmes, showing that they loved the environment and were concerned about solving the issue of climate change and its effects to the environment (Cotton et al, 2021). For example, they used the visual programming environment Scratch to have students create simulations in context of climate change with a focus on system and computational thinking (Mittenzwei et al, 2019).…”
Section: Related Programmes Trainings and Campaignsmentioning
confidence: 99%
“…In climate change education, strategies or learning methods that can influence the younger generation's behavior regarding climate issues are still being debated (Kolenatý et al, 2022). Mittenzwei et al (2019) assert that communities should be given the means to evaluate scientific evidence and comprehend the consequences of their actions, and this is especially vital for elementary and upper-level students, as they represent potential future leaders who must grasp and address the implications of climate change (Oliver & Adkins, 2020). Challenges related to the issue of climate change can be faced, one of which is by forming community climate literacy through education (Wu & Otsuka, 2021).…”
Section: Introductionmentioning
confidence: 99%